Micromechanical modelling of advanced hierarchical composites - Griffiths, Emma (Department of Mechanical Engineering, 2020)
Nanoporous metals are uniquely interesting materials. Their high ductility and impressive strength in compression make them a favourable candidate for use in structural applications. However, these materials under-perform when tested in tension. This issue may be addressed by impregnating the nanoporous metal with a polymer. In this work the behaviour of a polymer impregnated nanoporous gold (NPG) composite is explored using the finite element method in three different scenarios: linear elasticity, fracture and electrically stimulated actuation. Using representative volume elements (RVEs), previously unexplored relationships between the macroscopic material response and its microstructure as well as interesting mechanisms and deformation strategies are explored. Firstly the homogenization and micromechanical response under compression of a gold/epoxy nanocomposite is investigated. Investigation into the stress-strain response within the material reveals a complex interaction between the constituents resulting in both compressive and tensile strains. With specific focus on the loading modes of the individual ligaments, significant axial and bending loading as well as an unexpectedly large amount of shear stress is seen. Following this the improved ductility and resistance to fracture of a gold/polymer nanocomposite compared to the pure NPG material is revealed using computational compact-tension tests. It is observed that the polymer stabilizes the gold thus preventing ductile fracture. Several toughening mechanisms are also revealed. Previously unexplored effects of increasing the volume fraction on the ductility and strength of the composite are also explored. The functionality of the gold/polymer nanocomposite as an actuator material is then investigated. A coupled chemo-electro-mechanical material model is adopted to model the electrically stimulated deformation. This is carried out in Abaqus using a novel staggered explicit-implicit solution scheme. Simulation of several RVEs with different gold volume fractions show that while the gold provides strength and support, increasing its volume fraction hinders both the ion transport speed and the total deformation of the nanocomposite. A complex interaction between the stress response and the gold volume fraction is also observed.